The Understanding of Electrical and Computer Engineering Students to Translate Sharia Economic Texts Via Google Translate - Adria, Agus (PT. Anagata Sembagi Education, 2024)
The potential of Islamic economics to develop in Aceh where Islamic culture and values ​​are very large and strong. Therefore, even though electrical and computer engineering students do not specifically study Islamic economics courses but live in Aceh, it is important to know the insight into Islamic economic texts. Google translate is very helpful in translating texts with nuances of sharia economics in Aceh to electrical and computer engineering students. This research was a descriptive-qualitative. The data used as a test comes from the abstract of an article by Ode and Hamizar (2024) entitled